Fracture mechanics analyses of the slip-side joggle regions of wing-leading-edge panels - Kyongchan Song; Dawn R. Phillips; Norman F. Knight, Jr.; Ivatury S. Raju (Fracture and Structural Integrity)
The Space Shuttle wing-leading edge consists of panels that are made of reinforced carbon-carbon. Coating spallation was observed near the slip-side region of the panels that experience extreme heating. To understand this phenomenon, a root-cause investigation was conducted. As part of that investigation, fracture mechanics analyses of the slip-side joggle regions of the hot panels were conducted. This paper presents an overview of the fracture mechanics analyses.